Digital Storytelling as a Dual-Domain Pedagogical Strategy: A Systematic Review of Its Effects on Speaking Skills and Emotional Literacy in Primary Education - Imas Masrini; Ninah Hasanah; Lucky Rahayu Nurjamin (Papanda Publisher, 2026)
Despite growing recognition of digital storytelling as a promising pedagogical approach, its simultaneous effects on speaking skills and emotional literacy in primary education remain insufficiently synthesized, particularly within the Indonesian schooling context. This systematic literature review examined 20 peer-reviewed international studies published between 2018 and 2025, retrieved from Scopus, Frontiers, and PubMed databases. Articles were selected through structured inclusion and exclusion criteria with inter-rater reliability confirmed at κ = .82, and data were analyzed using Braun and Clarke's six-phase thematic analysis framework. Results indicate that 80% of reviewed studies reported significant speaking skill improvements — with mean score gains of 25–45% — across articulation, fluency, narrative structure, and expressive intonation. Emotional awareness was the most consistently documented affective outcome, reported in 90% of studies. Unanticipated findings included incidental vocabulary acquisition through collaborative scriptwriting and reduced socially avoidant behavior. These outcomes affirm that digital storytelling simultaneously cultivates communicative competence and emotional intelligence, aligning with sociocultural learning theory and Goleman's emotional intelligence framework. The findings support integration of digital storytelling within Indonesia's Merdeka Curriculum, with teacher professional development and equitable digital infrastructure identified as critical enabling conditions. Future research should prioritize longitudinal experimental designs and AI-integrated storytelling frameworks.